Hello,

-->

(for more comfort)

--->

~~~~~~~~~~

The first term will use the product rule since there are y and z in it, considering x as a constant and y as the variable.

Thus the derivative of the first term will be :

The red dots correspond to the derivative of yz. We have to use the product rule.

--->

--------->

~~~~~~~~~~

Now considering the second term

We have to use the product rule too.

--------->

~~~~~~~~~~

Now, the third term, z.

Its derivative is z' (3)

------------------------------

The derivative of the whole thing will be

And... I won't copy it, you can do it

I hope there is no mistake, check it again, it will make a good exercise